Features of Phraseological Units In Translation From English Into Uzbek (Based on The Novel "Days gone by" by Abdulla Kadiri) - Sattorova Fazilat Ermamatovna (Academicia Globe: Inderscience Research, 2026)
Phraseological expressions constitute the general vocabulary of the language and are important for the culture of the two peoples. This research work discusses some methods of translating phraseological units from English into Uzbek. Nowadays, phraseological expressions are considered necessary for new technologies, scientific and technical fields, and the translator is required to find a suitable equivalent in the translation process. The main purpose of the article is to analyze the concepts of the essence of phraseological units, describe various approaches to the study of their national and cultural identity, classify phraseological units in order to identify the main sources of national and cultural identity, and also analyze their expression in English artistic imagery